Perceptions of Curriculum, Faculty, and Institutional Support in Cambodian Postgraduate Programs - Wiputra Cendana; Keun Im; Evan Kurnia Alim (The Indonesian Institute of Science and Technology Research, 2026)
This study offers a comprehensive analysis of key determinants shaping the quality of postgraduate education in Cambodian universities. Using original survey data from 431 postgraduate students across three leading institutions, we investigate perceptions of curriculum structure, faculty competency, and institutional support. Findings reveal high reliability in the identified constructs, moderate-to-strong positive perceptions of curriculum and faculty, and nuanced views toward institutional resources and research environment. The analysis, anchored in established theoretical frameworks and underpinned by advanced quantitative methods, provides actionable insights for policymakers and academic leaders seeking to enhance postgraduate outcomes in the Global South context.